2014
DOI: 10.3109/16066359.2014.920013
|View full text |Cite
|
Sign up to set email alerts
|

A review of the literature concerning HIV and cigarette smoking: Morbidity and mortality, associations with individual- and social-level characteristics, and smoking cessation efforts

Abstract: Cigarette smoking is endemic among many populations, but is especially prevalent among people living with HIV, and is consequently associated with a variety of types of morbidity as well as mortality. Despite this knowledge, relatively little research has been conducted among smokers living with HIV. Extant research has focused on examining individual-level characteristics associated with smoking behaviors, to the neglect of examining social-level factors. This manuscript represents a critical literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 99 publications
1
18
0
Order By: Relevance
“…Thus, individuals with high anxiety sensitivity who use tobacco as a coping method may be increasing their risk for aversive mental health and physical health symptoms, and may in turn, be placing themselves at a greater risk for other maladaptive health behaviors (e.g., alcohol abuse, risky sexual behavior, and deliberate self-harm) to cope with such distress. This type of perspective is consistent broadly with syndemic models of HIV (Pacek & Crum, 2015). Thus, anxiety sensitivity-health behavior and health outcomes may be particularly robust among smokers compared to non-smokers.…”
supporting
confidence: 82%
“…Thus, individuals with high anxiety sensitivity who use tobacco as a coping method may be increasing their risk for aversive mental health and physical health symptoms, and may in turn, be placing themselves at a greater risk for other maladaptive health behaviors (e.g., alcohol abuse, risky sexual behavior, and deliberate self-harm) to cope with such distress. This type of perspective is consistent broadly with syndemic models of HIV (Pacek & Crum, 2015). Thus, anxiety sensitivity-health behavior and health outcomes may be particularly robust among smokers compared to non-smokers.…”
supporting
confidence: 82%
“…Smoking impacts on the immune system's capacity to mount an appropriate immune and inflammatory response to infections such as CAP, and this effect has also been observed in passive smokers (22,29,30). Some studies have suggested that there is an association between smoking and a poor virological and immunological response to ART (31)(32)(33)(34). This was confirmed in a recent study by Hile et al (35), who studied the It has been reported that approximately 25% of HIV-infected patients have chronic obstructive pulmonary disease (36).…”
Section: Risk Factors For Capmentioning
confidence: 99%
“…Within the United States, approximately 40% of the HIV-1-infected population are current smokers 15 , 16 . Despite the use of highly active antiretroviral therapy (HAART), smoking is known to exacerbate morbidity and mortality in HIV-1 patients 16 – 18 . In HIV-1 patients, smoking further weakens the immune system resulting in a higher risk of virological rebound, an increased rate of immunologic failure, and a decreased response to HAART 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%